PENGATUR LAMPU LALU LINTAS SISTEM DIGITAL BERBASISKAN MIKROCONTROLER - Suryadi Suryadi (Elektron : Jurnal Ilmiah, 2009)
traffic light still uses analog system with discrete component. This technology has many disadvantages for example difficulty in maintenance and repair, display only to lamp without counter and no control for delay in normal hours or rush hours. These can be cause traffic jam and accident. To solve this problem, traffic light system is completed by digital system and buzzer using microcontroller AT89C51. The observation result to prototype at laboratory in Polytechnic State of Padang show this system can be implemented to real condition.